Brainstorm Pipeline Analysis of Resting-State Data From the Open MEG Archive - Niso, Guiomar; Tadel, Francois; Bock, Elizabeth; Cousineau, Martin; Santos, Andrés; Baillet, Sylvain (Frontiers in Neuroscience, 2019)
We present a simple, reproducible analysis pipeline applied to resting-state magnetoencephalography (MEG) data from the Open MEG Archive (OMEGA). The data workflow was implemented with Brainstorm, which like OMEGA is free and openly accessible. The proposed pipeline produces group maps of ongoing brain activity decomposed in the typical frequency bands of electrophysiology. The procedure is presented as a technical proof of concept for streamlining a broader range and more sophisticated studies of resting-state electrophysiological data. It also features the recently introduced extension of the Brain Imaging Data Structure (BIDS) to MEG data, highlighting the scalability and generalizability of Brainstorm analytical pipelines to other, and potentially larger data volumes.